Conflits terriens et réforme agraire dans la plaine de l’Artibonite (Haïti) - Michael Levy (Cahiers des Amériques Latines)
The Haitian Government has initiated the execution of the agrarian reform in the Artibonite Valley. This district has witnessed important land conflicts since irrigation works have been carried out in the fifties, giving much greater value to these rice-growing lands. The objective proclaimed by the Haitian Government is to obtain support from the peasants through local committees in order to redistribute the contested land or the state land, to end the violence and to raise rice production. This programme confronts an enormous demographic pressure, the entanglement of land tenure systems and the antidemocratic political traditions, exacerbated by corrruption and patron-client relations that instill and pervert the peasant participation models and the self-help structures.